Experimental and modeled analysis of contaminant mobility in coal fly ash landfills under continuous rainfall regimes - Shuyuan Xu; Yongbo Zhang; Jiangbo Guo; Aijing Wu; Xinghua Xiang; Haodong Sun (Scientific Reports)
Abstract In China, a significant amount of coal fly ash is stored or used for landfill reclamation. The contaminants in coal fly ash (CFA) leachate can cause regional soil and groundwater contamination during long-term storage. This paper focuses on a coal gangue comprehensive utilisation power plant in Fenyang City, Shanxi Province, China, where the leaching characteristics of CFA were investigated by leaching tests. Laboratory-scale long-term soil column leaching tests and long-term ash column leaching tests were conducted using compacted soil and compacted CFA, respectively, to simulate contaminant migration patterns from CFA during the early and later stages of landfill operation. Hydrus-1D simulation software was used to calculate contaminant transport from the CFA landfill. The test results indicate that the concentrations of six representative elements or compounds in the CFA leachate exceeded the Groundwater Standard Class III. Among these contaminants, Pb contamination was the worst, with concentrations 26.67 times above the standard. The flow rate of the leachate is lower when the degree of compaction of the Ma’lan loess and the CFA is higher, and it takes longer for the leachate to start flowing. The greatest release of the ions occurred at a Ma’lan loess compaction coefficient of 0.943 and a hydraulic conductivity of 6.031 × 10− 7. Under extreme rainfall conditions, the contaminants and heavy metals in the fly ash leachate migrate to a maximum depth of 56 cm in the compacted soil layer, with Pb reaching a depth of 28 cm, nickel 23 cm, cadmium 9 cm and hexavalent chromium 5 cm to meet Class III groundwater quality standards. These results indicate a potential risk of groundwater contamination in the vicinity of CFA deposits or land reclamation projects in long-term storage. To mitigate this risk, the Guofeng Power Plant may consider utilizing locally compacted Malan loess in combination with geosynthetic materials or implementing a liner much thicker than 1.5 m to enhance the impermeability of the fly ash landfill.